2021
DOI: 10.35308/jbkan.v5i2.4367
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Peningkatan Literasi Dan Inklusi Keuangan Bagi Masyarakat Agraris Di Kawasan Pedesaan

Abstract: The government's objective to increase financial literacy and inclusion should be supported by the stakeholders. The increasing of financial inclusion and literacy play important role to generate community livelihood. Currently, the level of financial inclusion and literacy in Indonesia are diverse. It depends on many factors such as where they are living, in urban area or country site. In urban areas, the financial literacy index reaches 41.41 percent and the level of financial inclusion reaches 83.60 percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
1
0
3
Order By: Relevance
“…Dengan adanya dana desa, setiap desa di Kabupaten Sleman sekarang memiliki lebih banyak otonomi dalam perencanaan dan pengelolaan keuangan, serta pembangunan desa (Safitri & Fathah, 2018;Zulbetti et al, 2019). Otonomi ini tidak hanya menandai langkah besar dalam pemberdayaan desa, tetapi juga menciptakan fondasi yang kuat bagi peningkatan kesejahteraan masyarakat desa di Sleman (Cahyaningtyas et al, 2020;Fahlevi et al, 2021).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Dengan adanya dana desa, setiap desa di Kabupaten Sleman sekarang memiliki lebih banyak otonomi dalam perencanaan dan pengelolaan keuangan, serta pembangunan desa (Safitri & Fathah, 2018;Zulbetti et al, 2019). Otonomi ini tidak hanya menandai langkah besar dalam pemberdayaan desa, tetapi juga menciptakan fondasi yang kuat bagi peningkatan kesejahteraan masyarakat desa di Sleman (Cahyaningtyas et al, 2020;Fahlevi et al, 2021).…”
Section: Pendahuluanunclassified
“…Pertama, terdapat kekurangan dalam regulasi dan petunjuk pelaksanaan yang menjadi panduan dalam pengelolaan keuangan desa. Kekurangan ini berpotensi menciptakan ketidakpastian dan ketidakkonsistenan dalam pelaksanaan anggaran di tingkat desa (Fahlevi et al, 2021;Maharani & Cipta, 2022), termasuk di Sleman. Kedua, evaluasi KPK menyoroti adanya potensi masalah dalam tata laksana, termasuk pemahaman yang kurang mengenai kerangka waktu dan transparansi dalam proses manajerial (Cahyaningtyas et al, 2020;Safitri & Fathah, 2018).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Furthermore, in the third indicator, knowledge about insurance found that the informants only knew about insurance in general. Because they know insurance only in general, their level of trust in using insurance is very minimal, even though according to (Fahlevi et al, 2021) a high level of financial literacy can help agrarian communities in choosing financial products that best suit their needs. Agrarian communities can access a variety of financial services, including agricultural insurance and financing for agricultural activities.…”
Section: Figure 2 Financial Literacy Farmers Must Havementioning
confidence: 99%